2020
DOI: 10.1101/2020.08.20.260083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maladaptive myelination promotes epileptogenesis in absence epilepsy

Abstract: Neuronal activity can influence the generation of new oligodendrocytes (oligodendrogenesis) and myelination. In health, this is an adaptive process that can increase synchrony within distributed neuronal networks and contribute to cognitive function. We hypothesized that in seizure disorders, aberrant neuronal activity may promote maladaptive myelination that contributes to pathogenesis. Absence epilepsy is a disease defined by increasingly frequent behavioral arrest seizures over time, thought to be due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 111 publications
1
5
0
Order By: Relevance
“…It is thought that dysregulation of either developmental or activity dependent myelination can contribute to status epilepticus onset and the progression to epilepsy, and that seizure itself can promote dysregulation of remyelination, increasing pathological circuit function that promotes further epileptic activity (Gibson, et al, 2017). Indeed, a recent paper has found that remyelination during epilepsy supported the recurrence of seizures, suggesting that remyelination is contributing to disease pathology over time (Knowles, et al, 2022). Our findings suggest that part of this mechanism may be due to the changes in neuron to OPC connections, which may be instructive for myelination, and are lost after seizure.…”
Section: Discussionsupporting
confidence: 52%
“…It is thought that dysregulation of either developmental or activity dependent myelination can contribute to status epilepticus onset and the progression to epilepsy, and that seizure itself can promote dysregulation of remyelination, increasing pathological circuit function that promotes further epileptic activity (Gibson, et al, 2017). Indeed, a recent paper has found that remyelination during epilepsy supported the recurrence of seizures, suggesting that remyelination is contributing to disease pathology over time (Knowles, et al, 2022). Our findings suggest that part of this mechanism may be due to the changes in neuron to OPC connections, which may be instructive for myelination, and are lost after seizure.…”
Section: Discussionsupporting
confidence: 52%
“…Myelination deficiencies have been found in several neurologic disorders in particular in multiple sclerosis [41] and are often associated with seizure occurrence [42]. There is increasing awareness that also in epilepsy maladaptive myelination or axon demyelination are of high relevance for seizure generation [19,18].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Knowles et al [18] found increased oligodendrogenesis and myelination in an animal model for absence seizures and demonstrated that it contributes to epilepsy progression. In contrast, we found in our human FCD IIa cases thinner myelin sheaths in layer V/VI of the temporal lobe [24] and, as shown here, of the frontal lobe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…neuronal over-excitation is considered an essential feature across different types of epileptic seizure models (Knowles et al, 2022). Thus, an improved understanding of the mechanisms underlying seizure progression, particularly neuronal overactivation, could facilitate the development of innovative anti-epileptogenic treatment strategies.…”
Section: Introductionmentioning
confidence: 99%